A ideia de concepção pública de justiça: entre John Rawls e Michael Sandel - Lazaroto, Lucas Gustavo (2023)
Our research aimed to investigate the justification criteria for a public conception of justice. We focused the research on what came to be known as the liberal-communitarian debate that took place in the 1980s, especially after Michael Sandel critique of John Rawls political liberalism. The investigation that follows is relevant, as the key element of the debate is to define a criteria to justify the formation of State policies. Conceptual-ly, we seek to discuss the idea of the priority of justice to the detriment of the common good, since the plural character of contemporary democracies makes it difficult to find a single conception of the common good to support a public conception of justice. Methodologically, we organize our research into three chapters. First, we present Rawls theory of justice as fairness from the two stages of his work, especially A Theory of Justice and Political Liberalism. Afterwards, we discuss the communitarian critique, mainly from Michael Sandel critique in Liberalism and the Limits of Justice. Finally, we evaluate the debate between Rawls and Sandel. That said, Rawls formulations, from the publication of A Theory of Justice in 1971, established a new paradigm for the philo-sophical investigation of the respective area of study. Rawls fundamental claim is the reformulation of the social contract theory from the perspective of social justice and has as its content two principles of justice: the principle of egalitarian freedom and the sec-ond containing the fair equality of opportunity and the difference principle. For this to be possible, Rawls makes use of a hypothetical and ahistorical situation to justify his princi-ples of justice, the original position, where the parties, under a veil of ignorance, will chose the principles of justice as fairness. Although the rawlsian formulation is powerful, it has not been exempted from criticism and, among the main ones, is that made by Michael Sandel. Sandel does not disagree with the assumptions of social justice, bit with the way in which Rawls established his justification criteria. In the author`s perspective, the conception of justice cannot precede the conception of good, as this would imply the existence of an atomized person, a “unencumbered self”. Sandel understands that Rawls flaw is characteristic of all (liberal) deontological theories, as it is the constitute characteristics of people that allow them to agree on the content of the political obliga-tions that will govern their lives, since they know and share certain practices. That said, we evaluated Sandel criticism directed at Rawls and found that the two authors disa-greed on some conceptual aspects. This led us to compare the interpretations of Rawls provided by Sandel to verify the authors conceptual understandings. After all, we con-clude that Sandel criticism has great relevance for the contemporary debate and de-serves to be taken in account, but the author was mistaken to interpret rawlsian theory as purely deontological, universalist and applicable to any type of society.